Expression of deubiquitinase genes and inflammatory response in myeloid leukemia - Thanh Huyen, Nguyen; Hoang Giang, Nguyen; Thi Xuan, Nguyen (Vietnam Journal of Biotechnology, 2022)
Myeloid leukemia (ML) is a cancer of the blood that begins when cells of the myeloid lineage uncontrollably change and grow. Acute myeloid leukemia (AML) is a disorder of rapid, uncontrolled growth of immature myeloid cells in the blood and bone marrow. Chronic myeloid leukemia (CML) is characterized by the aberrant proliferation of myeloid cells and driven by the translocation of regions of the BCR and ABL genes to form the Philadelphia (Ph) chromosome. The deubiquitinase enzymes (DUBs) including A20, OTUB1, OTUB2, and Cezanne play important roles in inhibiting NF-κB activation in response to various stimuli. Cytokines including tumor necrosis factor-alpha (TNF-α), IL-6, and IL-1β are released from immune cell activation triggered by antigenic stimulation. To this end, blood samples of 20 AML and 62 CML patients and the control group consisting of 37 healthy individuals were used to examine the mRNA expression of A20, OTUB1, OTUB2 and Cezanne genes by using quantitative RT-PCR and determine IL-6, TNF-α and IL-1β concentrations by using ELISA. As a result, the mRNA level of OTUB1 was significantly decreased in both AML and CML patients compared to that in healthy individuals, however, no difference in the transcriptional expression of OTUB2 among AML and CML patients and control group was detected. Unlike the levels of OTUB1 and OTUB2, the expressions of A20 and Cezanne in CML, but not in AML patients were significantly lower than healthy individuals. For serum cytokine analysis of the study groups, in AML and CML samples, IL-6 and TNF-α concentrations significantly increased in comparison with the control group, however, IL-1β level was similar among CML, AML patients and healthy individuals. In conclusion, this study revealed the different DUB involvement in the pathogenesis of ML, suggesting further investigations on gene polymorphisms and their functions linked to biological properties of leukemia cells.